Ecological Da’wa as an Alternative for Development Communication - Prastyo, Dany Tantowi (Universitas Muhammadiyah Yogyakarta, 2023)
Environmental issues occurred from the end of the 20th century until the second decade of the 21st century. Environmental issues such as the climate crisis, global warming, and exploitation of natural resources are separate problems in human development. The development required a public participatory process so that the development comes can run effectively and efficiently, especially development based on an ecological perspective. Indonesia, with the largest Muslim population in the world, has the potential to support a development process based on an environmental perspective. Islam, by the Al-Qur’an as the base of guiding, contains ecological values that need to be transformed for Muslims. The process of transforming the values of Islamic guidance, or da’wa, allows for the transformation of Islamic values, especially ecological values, which are then referred to as ecological da’wa. In ecological da’wa, the process and end goal can be an alternative development communication to create a sustainable living environment and make the community achieve sustainable and harmonious prosperity and welfare.